Formative Assessment Performed by High School Teachers in the Pandemic Era - Hasti Robiasih; Titi Lestari (Loquen, 2020)
AbstractAssessment is an integral part of the learning and teaching process. Effective formative assessment is intended to improve students’ achievement and raise teacher’s quality. However, qualified formative assessment is rarely performed in a real classroom in this pandemic era. This paper describes how senior and vocational high school teachers conduct a formative assessment in this pandemic era. It focuses primarily on the type of task and activity offered, language skills and components covered, the fulfillment of good criteria of assessment, the development of students’ critical thinking, also the strengths and weaknesses of the assessment. The data collected by means of documents assessment created by the teachers. Data analysis was conducted by employing Miles, Huberman, and Saldana’s theory. The results indicate the teachers conducted formative assessment mostly via Google Classroom and WhatsApp. In assessing speaking and reading, teachers provide various texts followed dominantly by multiple choices tests. In writing, students are assigned to share their feeling and opinion about a movie or current topic and write texts based on picture series. Teachers also employed form-focused grammar activities. It is evident that some tasks promote students’ critical thinking. However, some tasks are not well-constructed in terms of suitability with basic competence, time allotment, and the level of difficulties. Therefore, it is questionable whether the purpose to make changes to instruction can be achieved or not.Keywords: changes to instruction, formative assessment, Google Classroom, pandemic era